Parasitic light absorption, rate laws and heterojunctions in the photocatalytic oxidation of arsenic(III) using composite TiO2/Fe2O3 - Bullen,JC; Heiba,HF; Kafizas,A; Weiss,DJ (Chemistry: A European Journal, 2022)
Composite photocatalyst-adsorbents such as TiO2/Fe2O3 are promising materials for the one-step treatment of arsenite contaminated water. However, no previous study has investigated how coupling TiO2 with Fe2O3 influences the photocatalytic oxidation of arsenic(III). Herein, we develop new hybrid experiment/modelling approaches to study light absorption, charge carrier behaviour and changes in the rate law of the TiO2/Fe2O3 system, using UV-Vis spectroscopy, transient absorption spectroscopy (TAS), and kinetic analysis. Whilst coupling TiO2 with Fe2O3 improves total arsenic removal by adsorption, oxidation rates significantly decrease (up to a factor of 60), primarily due to the parasitic absorption of light by Fe2O3 (88% of photons at 368 nm) and secondly due to changes in the rate law from disguised zero-order kinetics to first-order kinetics. Charge transfer across this TiO2-Fe2O3 heterojunction is not observed. Our study demonstrates the first application of a multi-adsorbate surface complexation model (SCM) towards describing As(III) oxidation kinetics which, unlike Langmuir-Hinshelwood kinetics, includes the competitive adsorption of As(V), and we further highlight the importance of parasitic light absorption and catalyst fouling when designing heterogeneous photocatalysts for As(III) remediation.